2015
DOI: 10.1039/c4nr06032f
|View full text |Cite
|
Sign up to set email alerts
|

VO2nanorods for efficient performance in thermal fluids and sensors

Abstract: VO2 (B) nanorods with average width ranging between 50-100 nm are synthesized via a hydrothermal method and the post hydrothermal treatment drying temperature is found to be influential in their overall phase and growth morphology evolution. The nanorods with unusually high optical bandgap for a VO2 material are effective in enhancing the thermal performance of ethylene glycol nanofluids over a wide temperature range as is indicated by the temperature dependent thermal conductivity measurements. Humidity and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Sensing mechanisms previously used to describe the responses of vanadium oxide based sensors 12 were found to be applicable in this study in conjunction with those applied to other metal oxide devices operating at room temperature.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Sensing mechanisms previously used to describe the responses of vanadium oxide based sensors 12 were found to be applicable in this study in conjunction with those applied to other metal oxide devices operating at room temperature.…”
Section: Introductionmentioning
confidence: 96%
“…Strelcov et al reported that by operating a VO2 nanowire sensor close to the materials' metal-semiconductor transition temperature (≈ 68 ̊ C), conductance through the material became highly sensitive to the molecular composition of the environment, even enabling the detection of inert gases 13 . Depending on the structures formed and their respective oxidation states, vanadium oxides can also display sensitivity to water (H2O) and are thus suitable for use as humidity sensors 12,14,27,28 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations